Colonial Andean Memory : Indigenous and mestizo writers of the 16th and 17th centuries - Herrera Villagra, Alejandro (2020)
Three excellent writers, Garcilaso de la Vega, Juan de Santa Cruz Pachacuti Yamqui and Felipe Guaman Poma, managed to register a transcendent remembrance of andean antiquity. We postulate that in the Comentarios Reales de los Incas (Royal Comments of the Incas) [1609], the Relación de Antigüedades deste Reyno del Pirú (Relation of Antiques in this Realm of Peru) [1613], and the Nueva Corónica y Buen Gobierno (New Chronicle and Good Government) [1615], they built a memory of the past claimed in spite of the coloniality of its time. This fact has prompted us to interpret the circumstances in which the history and culture of the peoples of the Andes during the XVI century underwent a series of transformations and to explain how an ethnic identity transcended through the historic writings.